Adjudication of Fibromyalgia Syndrome: Challenges in the Medicolegal Arena - Mary-Ann Fitzcharles; Peter A Ste-Marie; Angela Mailis; Yoram Shir (Pain Research and Management)
The medicolegal challenges surrounding fibromyalgia (FM) arise from the subjectivity of symptoms, causal attribution and reported symptoms sufficiently severe to cause disablement. In the present article, the authors have endeavoured to provide clarification of some current issues by referencing the current literature, including the 2012 Canadian Fibromyalgia Guidelines. While FM is accepted as a valid condition, its diagnosis is vulnerable to misuse due to the subjectivity of symptoms. Without a defining cause, a physical or psychological event may be alleged to trigger FM, but adjudication of causation must be prudent. Although some individuals may experience severe symptoms, the prevalent societal concept of disablement due to FM must be tempered with the knowledge that working contributes to psychosocial wellbeing. Evidence provided in the present report may assist the courts in reaching decisions concerning FM.